THE EFFECT OF EDUCATIONAL PRACTICES ON NIGERIAN TERTIARY STUDENTS’ PERFORMANCE IN STATISTICS - Adelodun, Olusegun Ayodele (Advances in Social Sciences Research Journal, 2017)
The study focused on effects of educational practices on tertiary students’ performance in statistics. The study aimed at examining the existing relationships between educational activities and affairs, which affects performance of students in statistics. The study adopted a case study research design. The population of the study comprised students of Obafemi Awolowo University, Ile-Ife. The sample of the study was 100 students from five Faculties in Obafemi Awolowo University, Ile-Ife. The sampling technique used was simple random sampling. A self-designed questionnaire was developed and administered to the randomly selected departments for the data collection. The research instrument used for this research was validated by the researcher’s supervisor. The questionnaire was personally administered by the researcher. The data obtained was analyzed using descriptive statistics. The findings revealed that majority of the students 90(90%) agreed that there is relationship between teaching method and tertiary students’ performance in statistics, 89(89%) of the respondents agreed that correlation exists between outcome of assessment using distributed practice homework and massed practice homework. The study also revealed that majority of the students 82(82.0%) believed that teacher’s characteristics affect students’ performance in statistics. It was also discovered that a good number of students 74(74%) attested to it that there is significant effect of institutional constraint on performance of students in statistics. The study concluded that there are significant effects of educational practices on the performance of tertiary students in Statistics.